Application of the Mind Mapping Learning Model to Improve Student Learning Outcomes - Far-Far, Gazali; Kubangun, Nur Aida; Biczo, Gabor (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
Learning activities in Social Sciences subjects often cause students to lose focus during the lesson, thereby affecting learning outcomes. This is seen in student learning outcomes in the pre-cycle. Only 4 students, with a 20% achievement rate, met the Minimum Completion Criteria. Therefore, the purpose of this study is to describe the application of the Mind Mapping Learning Model in Social Studies learning to improve student learning outcomes. The research method used was Classroom Action Research (CAR), conducted in two cycles. Data collection used post-test questions, LKPD, teacher activity sheets, and student activity sheets. The study concluded that learning in Social Studies subjects with Hindu-Buddhist History material that applied the Mind Mapping learning model increased. In the first cycle, 11 students (55%) met the standard. In the second cycle, 20 students (100%) met the Minimum Completion Criteria. Therefore, it can be concluded that applying the Mind Mapping learning model in Social Studies subjects can improve student learning outcomes.